Adult exposure to ocean acidification and warming leads to limited beneficial responses for oyster larvae. (20th June 2021) - Gibbs, Mitchell C; Parker, Laura M; Scanes, Elliot; Byrne, Maria; O'Connor, Wayne A; Ross, Pauline M
Abstract: There is a need to understand the responses of marine molluscs in this era of rapid climate change. Transgenerational plasticity that results in resilient offspring provides a mechanism for rapid acclimation of marine organisms to climate change. This study tested the hypothesis that adult parental exposure to elevated p CO2 and warming will have transgenerational benefits for offspring in the oysters Saccostrea glomerata and Crassostrea gigas . Adult S. glomerata and C. gigas were exposed to orthogonal treatments of ambient and elevated p CO2, and ambient and elevated temperature for 8 weeks. Gametes were collected and fertilized, larvae were then reared for 9 days under ambient and elevated p CO2 . Egg lipidome and larval morphology and lipidome were measured. Parental exposure to warming and elevated p CO2 led to limited beneficial transgenerational responses for eggs and larvae of S. glomerata and C. gigas . Overall, larvae of S. glomerata were more sensitive than C. gigas, and both species had some capacity for transgenerational plasticity. This study supports the idea that transgenerational plasticity acts as an acclimatory mechanism for marine organisms to cope with the stress of climate change, but there are limitations, and it may not be a panacea or act equally in different species.